Role of Genetics in Anesthesiology - Ziske Maritska; Rani Iswara; Ignatius Aldo Winardi; Yuni Dwi Marantika; Irfan Ferdinand Tambunan; Lovina Lovina; Mgs. A. Rifqi Murtadho; Sendy Aditya Nugraha; Cendy Legowo; Victor Pulpa Seda; Awang Budi Saksono (Cell and BioPharmaceutical Institute, 2022)
One thing that differentiates one person from another is one’s genetic make-up. Genetic plays a role in every branch of medicine, including anesthesiology. An anesthesiologist must be well familiarized with hereditary (genetic) conditions, chromosomal traits, heredity-familial disorders, and even recessive variants because particular conditions might demand a different anesthetic and perioperative pharmacological management. These circumstances may lead to an opening of a rapidly expanding state of pharmacogenetics/genomics and its relevancy in anesthesia nowadays. This narrative review provides insight into the role of genetics in the field of anesthesiology.Keywords: genetics, anesthesiology, pharmacogenetics